An Age-Structured Model for the Effects of Temperature and Rainfall on the Transmission Dynamics of Malaria - Mapunda, Alanus; Mureithi, Eunice; Shaban, Nyimvua (Tanzania Journal of Science, 2024)
This study has investigated the impact of temperature and rainfall on the transmission dynamics of malaria using an age-structured population model, with a class of pregnant women. The equilibrium solutions have been analyzed, and numerical simulations carried out. The results show that there are significantly high rates of malaria infections for the temperature and rainfall ranging between (23.53 0C − 39.80 0C) and (14.82 mm − 38.44 mm) respectively. The results have shown that, the most affected populations are children up to five years old and pregnant women, and that decreasing the rate of transplacental transmission increases the number of children born free of malaria infections. Therefore, this work recommends human individuals to be aware of the variations of temperature, rainfall, and their corresponding ranges at which malaria transmission occurs most, so that they can take precautions.